1984
DOI: 10.1007/bf00379050
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of dose-effect relationships for vibration induced white finger in Japan

Abstract: Habitual use of many vibrating tools has been found to be connected with the appearance of various disorders affecting the blood vessels, nerves, bones, joints, muscles or connective tissues of the hand and forearm. The vibration exposures required to cause these diseases are not known exactly, either with respect to vibration intensity and the vibration frequency spectrum, or with respect to daily exposure time and total exposure period. The purpose of this study is to investigate available data on the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 3 publications
0
11
0
2
Order By: Relevance
“…Both overestimation and underestimation of the risk for VWF have been reported by investigators [16,21,24,60]. Risk overestimation has mainly been found in worker groups using tools with a predominantly lowfrequency percussive action, such as road breakers, rock drills, and stone hammers [4,6,21,56].…”
Section: The Risk-prediction Model In Iso 5349mentioning
confidence: 87%
“…Both overestimation and underestimation of the risk for VWF have been reported by investigators [16,21,24,60]. Risk overestimation has mainly been found in worker groups using tools with a predominantly lowfrequency percussive action, such as road breakers, rock drills, and stone hammers [4,6,21,56].…”
Section: The Risk-prediction Model In Iso 5349mentioning
confidence: 87%
“…Finally, "typical" daily vibration exposures are constructed from the frequencyweighted accelerations (either single axis component accelerations or the vibration total value) and exposure durations. Studies of the prevalence or latency of VWF (i.e., time of exposure prior to the onset of white fingers) have reported agreement with the prediction of the health risk as well as overestimation and underestimation of the risk 18,19) . The health risk appears to be overestimated for power tools such as rock drills, pavement breakers, sand rammers and impact wrenches, (e.g., see references 2,4,[20][21][22][23] , and underestimated for riveting tools and some grinders and chain saws (e.g., see references [24][25][26] .…”
Section: Introductionmentioning
confidence: 94%
“…The magnitude of vibration is considered to be one of the principal physical variables in¯uencing the severity of handtransmitted vibration [9]. Epidemiological studies have shown that the prevalence of VWF among workers using hand-held tools depends on the magnitude of the vibrations to which they are exposed: increasing magnitude of vibration is associated with higher prevalence of VWF [3,7]. It is hence presumed that more intense vibration may aect peripheral ®nger circulation more severely.…”
Section: Introductionmentioning
confidence: 99%